Peningkatan Mutu Tanah Liat Sebagai Bahan Baku Pembuatan Batu Bata di Kelurahan Bukaka, Kabupaten Bone, Sulawesi Selatan - Irzal Nur; Sufriadin -; Purwanto -; Asran Ilyas; Aryanti Virtanti Anas; Nirmana Fiqra Qaidahiyani; Halilintar Rangga Swara; Reski Fausi Amanda (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
In Bukaka area, Bone Regency, South Sulawesi, Indonesia, a small scale industry of red-bricks with clay as the raw material is exist, which have been operated by the local people in generations for decades. From field observation, a problem was identified related to the quality of the bricks produced, which mostly not fulfilled the quality standards. The purpuse of this community service activiy is to conduct a series of laboratory tests to define and formulate recommendations in order to improve the quality of the raw material and the bricks. Methods of laboratory works performed in this activity include mineralogical analysis (XRD) and chemical analysis (XRF) for clay samples, as well as dimension test, baking test, colour, saline content, absorbtion, compressive strength and sound test for the bricks. The results showed that the clay material composed of feldspar, quartz, kaolinite, and calcite; with high content of iron (Fe2O3 up to 8.85%), thus it is recommended to conduct a decreasing grade of the iron content using magnetic separator method. Dimension of the bricks produced by the local workers were generally far above the quality standard; thus it is recommended to conduct an increasing size of the bricks, particulary in their thickness and width. For the bricks baking, it is recommended to perform an increasing temperature and duration of the baking in order to gain a better quality. Absorbtion of the bricks were also averagely low, 0.5-0.6 gr/dm2/minute, thus it needs to be treated carefully at the time of the raw material mixing. Uncompressed strength test of the bricks resulted average value of 24.47 kg/cm2, which indicated a Class-25 type of the bricks, and having a good quality of sound.